SYNTHESIS OF AZO COMPOUNDS DERIVATIVE FROM EUGENOL AND ITS APPLICATION AS A TITRATION INDICATOR - Bambang Purwono; Catur Mahardiani (Indonesian Journal of Chemistry, 2009)
The synthesis of azo compounds from eugenol has been carried out by diazotation reaction. The diazonium salt was produced by reaction of aniline and sodium nitrite in acid condition at 0-5 °C temperature to yield benzenediazonium chloride salt. The salt was then reacted with eugenol to produce the azo derivatives. The azo product was analyzed by IR, 1H-NMR, dan GC-MS spectrometer. The results showed that the reaction of benzenediazonium chloride with eugenol gave 4-allyl-2-methoxy-6-hydroxyazobenzene in 34.27% yield for 30 minutes reaction. The derivative of azo compound was dissolved in ethanol and then the color changing was observed in range of pH 9.8-11.1 from yellow to red. Application for titration indicator for acetic acid titrated with sodium hydroxide showed error less than 3.20% compared with phenol phtaline indicator.